Impact of soil transfer between test fields on fungal diversity and wood durability. (May 2014) - Råberg, U.; Terziev, N.; Daniel, G.
<x content-type="archive" xml:space="preserve">Abstract</x> The impact of soil transfer on fungal degradation of Scots pine was investigated using visual inspection, microscopy and DNA profiling. Two test fields in Simlångsdalen with similar soil characteristics were used. Soil has previous been used with the purpose to retain the beneficial original micro-organisms present to imitate field-trials during laboratory condition. We found that fungal degradation in mini-stakes exposed in transferred soil did not correspond to mini-stakes exposed in original soil. Moreover, the type of degradation in the mini-stakes exposed in transferred soil did not match mini-stakes exposed in the original soil. However, established degradation in areas neighbouring the transferred soil was comparable. The fungal community in mini-stakes also varied more between different years than within the field. This suggests that relocation of soil disrupts the original fungal community due to unavoidable mixing of the soil. Therefore, the beneficial micro-organism characteristics of soils is very difficult to transfer elsewhere.